Analisis Komparasi Pendapatan Usahatani Bawang Merah Semi Organik dan Anorganik di Desa Sukorejo Kecamatan Rejoso Kabupaten Nganjuk - Putri, Isfia Diana; Rizkiyah, Noor; Fitriana, Nisa Hafi Idhoh (Jurnal Pertanian Terpadu, 2025)
The goal of this study was to examine and identify the income discrepancies between semi organic and inorganic shallot farming in Sukorejo Village, Rejoso District, Nganjuk Regency. This study took place during the months of November and December 2024. Using the Slovin formula, a sample was determined from a population of 298 farmers, resulting in a selection of 75 farmers. This was then recalculated with Proportional Stratified Random Sampling, yielding 15 semi-organic farmers and 60 inorganic farmers. The data analysis methods that were used in this study are Analysis of Cost and Income. The average of production, prices, and income of semi organic shallot was 15.986 Kg/Ha, Rp. 11.097, and Rp. 106.559.833/Ha and inorganic shallot were 12.321 Kg/Ha, Rp. 10.726, and Rp. 74.443.365/Ha. The findings indicate that the production, selling price, and profits from semi-organic shallot farming surpassed those from inorganic shallot farming. This may be attributed to the fact that semi organic shallot farmers experienced greater revenue compared to their inorganic counterparts, while the total expenses for inorganic shallot farmers were higher than those for semi organic farmers. Consequently, the income generated from semi organic shallot farming exceeded that of inorganic shallot farming.